Forecasting Russian regional social-economic development and its adaptation to the world economy - Yuli Lipets; Andrei Treivish (European Regional Science Association (ERSA), 2002)
The combination of modern economic-geographical methods and methodological approaches is used for the social-economic forecasting. The two-dimensional language reguires the simultaneous description of basic characteristics of the object (system or process) and its distinct positioning on the territory and on the taxonomic scale of the spatial hierarchy. It provides the framework for methodological unity. The spatial analysis includes both the oldest comparative-geographical methods and the modern mathematical. These methods provide an adequate analysis of Russian social-economic regularities. Mathematical statistics was used to reveal the gobal synergetic effects that determine spatial development of the three main types of states, i.e. developed, developing and transitional economies. The paper shows that the fundamental feature of the Russian economy is the abolition of the low prices' system, which determined the overall Russian reality until 1992 and the deep inequilibrium of the supply prices today. This inequilibrium caused the disintegration of the Russian economic space, the local and regional market autonomy, and the flows of goods and passengers under their abrupt decline and redistribution. Under these conditions there are two main development trajectories for Russia: a) an inertia oriented towards the raw material production, with limited defense of the Russian market in the coordination with the WTO principles; b) an orientation towards innovational activities without a refuse from the support of the traditional exports and import substitute industries (taking into account their economic efficiency). The paper discusses mostly the second trajectory.
Keywords: 330